2004
DOI: 10.1128/jcm.42.5.2345-2346.2004
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Infection in a Healthy Infant Caused by Two Different Serotypes

Abstract: We present a case of invasive pneumococcal infection in a healthy 10-month-old infant from whom Streptococcus pneumoniae serotype 23F was isolated from the blood and serotype 23B was isolated from the cerebrospinal fluid. Both serotypes were penicillin nonsusceptible. Pulsed-field gel electrophoresis analysis demonstrated that the two serotypes had distinct DNA patterns, indicating that infection did not occur as a result of capsular transformation but as a result of a mixed infection with two distinct pneumoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(9 reference statements)
2
6
0
Order By: Relevance
“…We describe cases of invasive pneumococcal disease caused simultaneously by two different strains. This phenomenon has been reported by others mainly in immunocompromised patients or in young children (5)(6)(7). Similarly, in our study, children younger than 5 years and patients with underlying illness other than HIV were more likely to have dual-serotype infection compared to older individuals and those without underlying illness, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We describe cases of invasive pneumococcal disease caused simultaneously by two different strains. This phenomenon has been reported by others mainly in immunocompromised patients or in young children (5)(6)(7). Similarly, in our study, children younger than 5 years and patients with underlying illness other than HIV were more likely to have dual-serotype infection compared to older individuals and those without underlying illness, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to dual-serotype IPD cases reported previously where coinfecting isolates from the same patient were genotypically unrelated (5,6), the majority of our isolate pairs were different strains as indicated by unrelated sequence types. The core genome of each isolate clustered with genomes of other South African IPD isolates of the same serotype and sequence type.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, vaccine response (either achievement of protective cutoff concentration and/or adequate OT) for serotypes 23F and 6B were low in the primary study, and this finding has been recently confirmed in another cohort of preterm infants 20 . In addition, these serotypes are associated with invasive disease in infants and 6B is the most common serotype for breakthrough infection following vaccination 21, 22 . Second, the frequency of BSI in the preterm infant can be as high as 60% in the most immature infants 14 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been an alarming increase in recent years in the prevalence of penicillin- resistant S. pneumoniae and pneumococcal meningitis caused by penicillin non-susceptible S. pneumoniae . Thus far pneumococcal meningitis caused by high-level penicillin resistant strains (MIC = 4 ug/ml) accounts for only a small portion of the cases reported from various countries around the world [ 1 - 6 ]. A case of pneumococcal meningitis caused by a high-level penicillin resistant S. pneumoniae 19F recently occurred in a 5-year old boy in southern Taiwan.…”
Section: Introductionmentioning
confidence: 99%